1998
DOI: 10.1046/j.1365-2141.1998.00866.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of linear and orthogonal regression analysis for local INR determination in ECAA coagulometer studies

Abstract: International sensitivity index calibrations based on the W.H.O. recommended method depend on orthogonal regression analysis. As this is not readily available in statistical packages, comparison has been made with simple linear regression analysis in a study of coagulometer effects on the International Normalized Ratio (INR) at 155 European centres. Sets of seven lyophilized normal and 20 lyophilized artificially depleted abnormal plasmas were provided with five coumarin test plasmas and two European Concerted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
(25 reference statements)
0
8
1
Order By: Relevance
“…This is in contrast with conventional local ISI calibrations, which we showed previously gave inferior results with linear regression (30 ). The number of plasmas used in conventional ISI calibration is much greater than with the PT/INR Line, and any difference in results between orthogonal and linear regression would be increased.…”
Section: Discussioncontrasting
confidence: 39%
See 1 more Smart Citation
“…This is in contrast with conventional local ISI calibrations, which we showed previously gave inferior results with linear regression (30 ). The number of plasmas used in conventional ISI calibration is much greater than with the PT/INR Line, and any difference in results between orthogonal and linear regression would be increased.…”
Section: Discussioncontrasting
confidence: 39%
“…Linear regression was shown previously to be inappropriate compared with orthogonal regression in conventional ISI calibrations of coagulometer PT systems (30 ). In a linear regression model, we assumed the certified INRs (x axis) to have no error and to represent true values.…”
Section: Linear Vs Orthogonal Regressionmentioning
confidence: 99%
“…However, the use of nonstandardized protocols and materials has resulted in variations in the measurements of the coagulation parameters (4). Hence, various studies have been carried out to try to standardize the methodology with a view to obtaining a universal standard (3,5,6). Nevertheless, the current methods still rely on the static measurements of single end-point values and it has been suggested that no single protocol works with all forms of hypercoagulability and/or hypocoagulability (7); hence, slight modifications are still required to dissect the underlying mechanism(s) of coagulation.…”
mentioning
confidence: 99%
“…Stocks of rabbit plain IRP (RBT/90) and bovine combined IRP (OBT/79) had been exhausted and not replaced. The ECAA rabbit plain reference thromboplastin, EUTHR‐1 (ISI = 1.67), used in previous multicenter ISI studies [8,12–15], has therefore been substituted in the certification of the plasmas by the rabbit route in both the local ISI calibration and Direct INR. EUTHR‐1 had been certified previously in terms of the WHO rabbit IRP RBT/90 reference thromboplastin [16].…”
Section: Methodsmentioning
confidence: 99%